Parents' experiences of the UPCDC remote learning program - Ibit, Shiena Lou M.; Uggadan, Mirriam I. (Quezon City College of Home Economics, University of the Philippines Diliman, 2021)
The study seeks to document the remote learning experiences among parents of enrolled 3- to 5-year-old children in the UP hild Development enter, focusing on their roles in remote learning, their challenges in facilitating the program, and their strategies in addressing their identified challenges. Ten parents were selected through random sampling and voluntary sampling for a short survey and an individual semi-structured interview, which facilitated their narration of experiences in remote learning during a pandemic. Data were subjected to coding, and then thematically categorized which pre ented the shared experiences of the participants. Results show that parents mainly identified their roles as teachers, learners, and parents as they prioritized the remote learning of their preschool children. With the modification of their existing roles, parents encounter challenges in terms of resources, parent-factors, and child-factors to perform their roles. These challenges stem from pandemic restrictions, handled preschool age groups, and the )earning delivery method. In response, parents address their challenges through time management, resource management, parent adjustment, and child-related strategies to manage remote learning responsibilities and their different life aspects to enhance their delivery of learning to the children. With these, findings of the study can help equip parents · in facilitating their children's development and education and extend this to schools whose remote learning set-up is similar to the program of the UPCDC.
Thesis (B.S. Family Life and Child Development)--University of the Philippines Diliman
Keywords: Distance education -- Philippines -- Quezon City